National Recovery and Resilience Plan: Denmark - Holtze, Bjørn (Italian Labour Law e-Journal, 2022)
This article outlines Denmark’s implementation of the funds aimed at economic recovery after the Covid-19 crisis. Denmark applied only for grants, not loans, as the Danish economy is strong, and has not suffered significantly during the crisis. With this in mind, the article concludes that EU grants have had only a minor impact in the social dimension and the labour market.